METODE ISTINBAT AL-AHKAM AL-JASHASH PADA BAB RIBA DAN KONTEKSTUALISASI PENAFSIRAN HUKUM TERKAIT BUNGA PERBANKAN - Unggul Purnomo Aji (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2024)
This research is based on the ongoing debate among scholars, Islamic academics, and economists regarding the legal status of interest (bunga) in bank credit loans. The study explores the legal reasoning (istinbat al-ahkam) of al-Jashash as an initial reflection of how the ruling on riba was formulated. It also opens the possibility for contextual interpretations and the application of other methods of istinbat to bridge the gap between classical concepts of riba and the contemporary monetary context. This study uses library research and thematic (mawdhu’i) tafsir methodology, considering the data is literary and thematic in nature. The findings indicate that al-Jassas’s interpretation of riba involves both linguistic and contextual ijtihad, employing not only linguistic analysis but also an understanding of the socio-historical context before and after the revelation of the verses concerning riba. In general, al-Jassas specifies (takhsis) the Qur’anic verses with hadith, statements of the companions, and consensus (ijma) of scholars, concluding that riba nasi’ah (deferred/usury-based credit) is prohibited. However, this type of istinbat lacks sufficient theoretical depth to address the legal development of riba in today’s context, and thus requires modification through qiyas. Through qiyas, it is argued that modern bank credit is permissible due to the different legal rationale (‘illah) involved